2016
DOI: 10.1097/ncc.0000000000000241
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Human Papillomavirus DNA Self-sampling on the Uptake of Cervical Cancer Screening

Abstract: Background:The rate of uptake of the Papanicolaou (Pap) smear is generally low. Its causal relationship with human papillomavirus (HPV) DNA allows HPV DNA self-sampling to be used as an alternative screening tool for cervical cancer.Objectives:This study explored the acceptability of HPV DNA self-sampling and its impact on the rate of compliance with cervical cancer screening.Methods:A crossover randomized clinical trial was conducted in community-based clinics. Participants were allocated to 1 of the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 26 publications
1
30
0
1
Order By: Relevance
“…The results indicated that physician sampling was less likely to be preferred than self-administered cervicovaginal sampling for women who have never undergone Pap testing. This result matched a similar study 25 in which patients with no history of Pap testing were more inclined to selfsampling. This finding has important implications, as one of the target groups for improving cervical screening rates is non-attendees or those that have not participated in screening in any form.…”
Section: Discussionsupporting
confidence: 88%
“…The results indicated that physician sampling was less likely to be preferred than self-administered cervicovaginal sampling for women who have never undergone Pap testing. This result matched a similar study 25 in which patients with no history of Pap testing were more inclined to selfsampling. This finding has important implications, as one of the target groups for improving cervical screening rates is non-attendees or those that have not participated in screening in any form.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this review indicate that vaginal smear selfcollection is a well-accepted method that may increase participation in cervical cancer screening 10-22,24-27. However, no standardized questionnaire for evaluating the acceptability of this method exists 10-22,24-27, and better explanations regarding the performance of this method are necessary to improve patient participation in cancer screening 9,23.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of women 512 who have not had a Pap smear according to health care guidelines is higher among 513 certain minority populations such as American Indians and Asians, as well as those who 514 live below poverty level (National Center for Health Statistics, 2017). The use of self-515 collection for vaginal specimens for hrHPV screening has the potential to improve 516 patient access to care, lead to higher patient compliance than current cervical cancer 517 screening programs, and thus impact cervical cancer detection rates (Camilloni et al 518 2013;Verdoodt et al 2015;Wong et al 2016). 519…”
Section: Discussion and Conclusion 504mentioning
confidence: 99%
“…259 260 It was estimated that introducing self-sampling could increase participation rates of 271 cervical cancer screening by 6.5% (Wong et al 2016). In follow-up interviews with the 272 First Nations study participants described above, many women stated that self-sampling 273 removed key logistical barriers related to making a clinic visit, as well as removed the 274 physical and emotional discomfort of a Pap test (Zehbe et al 2017).…”
Section: Hc2 Hpv Assay and Several Pcr Amplification-based Tests Sucmentioning
confidence: 99%